Suppression of Matrix Metalloproteinase Production in Nasal Fibroblasts by Tranilast, an Antiallergic Agent, In Vitro - Toshiyuki Shimizu; Kenichi Kanai; Kazuhito Asano; Tadashi Hisamitsu; Harumi Suzaki (Hindawi Limited, 2005)
Allergic rhinitis is an inflammatory disease characterized by nasal wall remodeling with intense infiltration of eosinophils and mast cells/basophils. Matrix metalloproteinases (MMPs), MMP-2 and MMP-9, are the major proteolytic enzymes that induce airway remodeling. These enzymes are also important in the migration of inflammatory cells through basement membrane components. We evaluated whether tranilast (TR) could inhibit MMP production from nasal fibroblasts in response to tumor necrosis factor-α (TNF-α) stimulation in vitro. Nasal fibroblasts (NF) were established from nasal polyp tissues taken from patients with allergic rhinitis. NF (2×105 cells/mL) were stimulated with TNF-α in the presence of various concentrations of TR. After 24 hours, the culture supernatants were obtained and assayed for MMP-2, MMP-9, TIMP-1, and TIMP-2 levels by ELISA. The influence of TR on mRNA expression of MMPs and TIMPs in cells cultured for 12 hours was also evaluated by RT-PCR. TR at more than 5×10−5 M inhibited the production of MMP-2 and MMP-9 from NF in response to TNF-α stimulation, whereas TIMP-1 and TIMP-2 production was scarcely affected. TR also inhibited MMP mRNA expression in NF after TNF-α stimulation. The present data suggest that the attenuating effect of TR on MMP-2 and MMP-9 production from NF induced by inflammatory stimulation may underlie the therapeutic mode of action of the agent in patients with allergic diseases, including allergic rhinitis.